2018
DOI: 10.1039/c8tc01788c
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Au/iron oxide nanocrystal heterostructures: magnetic, plasmonic and magnetic hyperthermia properties

Abstract: Interface and morphology determine the magnetic, plasmonic and magnetic hyperthermia properties of Au/iron oxide nanocrystal heterostructures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…Iron oxide nanoparticles and their dispersions have attracted lot of attention due to their unique ability to change physicochemical properties under an external magnetic stimulus . This ability of magnetic nanoparticle dispersions are exploited for a variety of applications in heat transfer systems, magnetic hyperthermia based cancer therapy, miniature electronic cooling, , biosensors, catalysis, , and water treatment. In recent years, superparamagnetic nanoparticles have been emerged as important materials for theranostics and nanomedicine, owing to their combined abilities for diagnosis and therapeutics. For dispersions, the stability is an important criterion for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Iron oxide nanoparticles and their dispersions have attracted lot of attention due to their unique ability to change physicochemical properties under an external magnetic stimulus . This ability of magnetic nanoparticle dispersions are exploited for a variety of applications in heat transfer systems, magnetic hyperthermia based cancer therapy, miniature electronic cooling, , biosensors, catalysis, , and water treatment. In recent years, superparamagnetic nanoparticles have been emerged as important materials for theranostics and nanomedicine, owing to their combined abilities for diagnosis and therapeutics. For dispersions, the stability is an important criterion for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…A general synthetic procedure involves the thermal decomposition of metalorganic compounds or metal carboxylate complexes as the precursors in the presence of pre-synthesized metal, metal alloyFe 3 O 4 or FePt seeds in a liquid environment composed of a solvent (typically, ODE or phenyl ether) loaded with selected surfactants (usually, OLAC, OLAM and/or TOP) at 200–300 °C. Such a scheme has enabled access to hetero-dimer CNHSs with epitaxially bound domains with close-to-spherical and/or cubic shape, such as of Au–Fe 3 O 4 , AuAg–Fe 3 O 4 , PtPd–Fe 3 O 4 , AuPd–Fe 3 O 4 , AuPt–Fe 3 O 4 , AuCu–Fe 3 O 4 , Pt–Fe 3 O 4 , Ni–Fe 3 O 4 , Cu–Fe 3 O 4 , Ru–Fe 3 O 4 , Au–CoO, AuAg–CoO, Pt–CoO, Au–MnO, Ag–MnO, FePt–CoFe 2 O 4 , FePt–In 2 O 3 , FePt–Fe 3 O 4 , FePt–MgO, Au–In:CdO, FePt–In:CdO, Pt–In:CdO, Pd–In:CdO, Cu–CeO 2 , Cu–ZrO 2 and Cu–ZnO [ 99 , 218 , 219 , 224 , 230 , 231 , 232 , 233 , 234 , 237 , 238 , 239 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 ,…”
Section: Non-core@shell Heteromeric Architecturesmentioning
confidence: 99%
“…In these tests, Au could be selectively removed from Me-Fe 3 O 4 (Me = Au, AuPt) hetero-dimers with peanut- to dumbbell-like profiles by with I 2 -driven leaching at ambient temperature. As a result, hetero-dimers with peanut- to dumbbell-like profiles were transformed into two types of nanostructure products: (i) nearly spherical all-Fe 3 O 4 CNCs with a small concave region that corresponded to the space portion that was previously occupied by the nested Au domain of the starting hetero-dimer parents; (ii) peanut- and dumbbell-like solid/hollow all-Fe 3 O 4 homo-dimer CNCs, where the hollow compartment enclosed a tiny Pt nanocrystal as the residue of the etching of the Au or AuPt domain of the parent hetero-dimers) [ 235 , 238 , 256 , 257 , 258 , 262 ]. The obtainment of such unusual Fe 3 O 4 nanostructures with either engraved surfaces or with cavities upon selective metal leaching demonstrated that in a population fraction of the parent AuPt-Fe 3 O 4 and Au-Fe 3 O 4 CNHSs, the AuPt and the Au (hemi)domains, which had originally been assumed to be only partially nested into Fe 3 O 4 section, could either expose the vast majority of their ‘’free’’ surface directly to the liquid medium, or have it protected by thin, either porous or discontinuous (thus, permeable) layer of Fe 3 O 4 .…”
Section: Non-core@shell Heteromeric Architecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some additional examples where a metal seed is used include: Au/NiS x where Au is the core at the center of a nickel sulfide polyhedron; 127 Au/Fe 7 S 8 NPL; 128 Au/CuInS 2 disc, where an epitaxial relationship was achieved by reacting Cu(acac) 2 and In(acac) 3 with DDT (thiolated Cu( ii ) and In( iii ) precursors) and OY in the presence of OY-capped gold seeds to first nucleate CuInS 2 forming twin dots that evolved during the reaction at 200 °C to an epitaxial 0D fcc (cubic) gold/2D wurtzite (hexagonal) CuInS 2 disc ( Fig. 5g ); 129 Au/Fe x O y formed by reacting Fe(CO) 5 with OA, OY and Au seeds, followed by a subsequent carving of the gold domain using iodine; 130 Au/ZnO; 131 Cu/ZnO, where the zinc precursor, ligands and solvent allow formation of ZnO multipods ( Fig. 5h ), shell and pyramid over Cu NPs and nanoforest sheath over Cu NWs.…”
Section: Formation Of Binary Metal/semiconductor Hybrid Nanostructuresmentioning
confidence: 99%